PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS LEARNING CYCLE 5-E DILENGKAPI PETA KONSEP PADA MATERI SISTEM PENCERNAAN MANUSIA UNTUK SMP - Nilawati,, Nilawati,; Indriati, Gustina; Nerita, S.Pd, M.Pd, Siska (STKIP PGRI Sumbar, 2014)
ABSTRACT Worksheet in the school is not suitable yet with learning cycle target. Worksheet which used in the school can help teacher in learning process but not allof student use it, they is not intresting with it. Some of students are not understand the material. In learning process is needed suitable media and teaching material. One of teaching materials that can use is worksheet. This research aim to produce worksheet based learning cycle 5-E completed mind map at human digestyfus system at junior high school and produce valid and pratical worksheet. This research is development research which uses 4-D models and consist of 4 stages are define, design, develop and disseminate but in this research disseminat is not used. Kinds of the research is primer data that consist validation result and practicality. The tes result of validity of students worksheet based learning cycle 5-E complete mind map by validator show that this worksheet is very valid with main score is 89,20% . the test of result practicality of students worksheet based learning cycle 5 -E complete with mind maping by teacher show that this worksheet at practical criteria with main score 89,20% and then the test result of practicality that done by students show that the students worksheet at practical criteria with main score 91,25%. So that, can be concluded students worksheet based learning cycle 5-E at human digestyfus system is very valid and very practical.